Putting Organizational Culture at the Heart of Industrial–Organizational Psychology's Research Agenda on Sustainability: Insights From Iberoamerica - Alcaraz, Jose M.; Kausel, Edgar E.; Colón, Carlos; Escotto, Marco Iván; Gutiérrez-Martínez, Isis; Morales, Daniel; Prado, Andrea; Suárez-Ruz, Esperanza; Susaeta, Lourdes; Vicencio, Fabián E. (Cambridge University Press, 2012)
Ones and Dilchert (2012) make a very pertinent and urgent call: Industrial–organizational (I–O) psychology has the potential to make a significant contribution to a research and practice agenda that helps organizations foster environmental sustainability. In this commentary, we will argue that, in this quest, I–O psychology should give significant attention to an issue that is only marginally mentioned in Ones and Dilchert’s article: the creation of organizational cultures. Here, we will develop the idea of how culture, value creation, and competitive advantage are linked to environmental sustainability. We will briefly illustrate our arguments with findings from our case-study research in the hospitality industry in 13 Iberoamerican countries Copyright © Society for Industrial and Organizational Psychology 2012